Morphometry of Male Reproductive Organ and Sperm Evaluation of Belgian Blue Crossbreed Cattle as a Candidate of Superior Bull - Riyan Nugroho Aji; Panjono Panjono; Ali Agus; Budi Prasetyo Widyobroto; Tety Hartatik; I Gede Suparta Budisatria; Ismaya Ismaya; Akhmad Fathoni; Dwi Astuti; Sigit Bintara (Faculty of Animal Science, Universitas Gadjah Mada, 2020)
The purpose of this study was to observe the size of reproductive organ and to evaluate the sperm quality of Belgian Blue (BB) crossbreed cattle. This cattle are the crossbreeding result between a female Brahman Cross (BX) cattle inseminated with frozen semen from pure male BB cattle, by Artificial Insemination (IB) method, as a candidate of superior bull. The samples of this study were 2.5 years old (BB1), (BB2), and (BB3) crossbreed cattle. Its process involved general physical examination, genital organ inspection, sperm production, and quality assessment. The data obtained were analyzed through descriptive analysis. The results of this study were the three BB crossbred cattle showed the good appearance of normal reproductive organs with scrotum circumferences of each bull were 40.2 cm, 38.6 cm, and 39.8 cm respectively, and sperm quality of the good and the normal motility values of each bull were 82%, 81% and 80%, viability 84%, 83%, and 86%, and the sperm concentrations of each bull were 2.218 million/ml, 1.986 million/ml and 2.120 million/ml respectively. As a result, it could be concluded that those three BB crossbreed cattle are suitable for being used as a superior bull.